Malva neglecta Leaves Extract / Biodegradable Diblock Copolymer Blend Biocomposites: Physicochemical and Antioxidant Properties - Pekdemir, Sibel Selçuk (My University, 2023)
In this study, it is aimed to prepare a 1:1 ratio PLA blend with PEG-b-PCL diblock copolymer, which is intended to be used as a drug release and biomaterial, and to obtain a biocomposite film with M.neglecta extract in different ratios. The obtained biocomposite films were first characterized by the ATR-IR spectrum and the characteristic functional group signals of the polymers were determined. The thermal analysis results show that the plant extract reduces the thermal stability of the polymer blend. Calorimetric measurements can be interpreted as plant-doped biocomposite films decrease the Tg temperature of the polymer blend, that is, increase the interchain free volume of the polymers. It was observed that swelling degree and moisture content of the plant treated polymer blend biocomposite films decreased with increasing plant percentage, while water solubility increased. It was observed that the plant extract slightly improved this feature of the PEG-b-PCL/PLA blend film, which showed shape memory. Due to the phenolic compounds in the structure of M. neglecta, it increased the antioxidant activities of the biocomposite films by adding it to the polymer blend.
Keywords: Antioxidant activity; biocomposite; M.neglecta; poly ?-caprolactone; shape memory polymer; swelling degree